EU entrepreneurial learning: perspectives of university students. Issue 1 (4th March 2014) - Spiteri, Simeon; Maringe, Felix
Abstract : Purpose: – This study addresses the issue of teaching in entrepreneurship courses in selected European universities in Malta and the UK. The paper aims to explore the views of students in different educational institutions about their understanding of entrepreneurship and the pedagogical aspects of teaching it. Design/methodology/approach: – Qualitative case study data were collected through one-to-one interviews with 31 students engaged in entrepreneurship course in four educational institutions in Malta and the UK. Findings: – Students identified four essential components that reflect the nature of entrepreneurial education. These consist of pedagogy, content, assessment and role model lecturer. Pedagogy of entrepreneurial courses was broadly seen as a mixture of traditional teaching and entrepreneurial learning. Students showed a preference for content aimed at developing creativity in practice-based situations. Preferred assessment strategies included individual assignments perceived as useful to deepen the concepts learned and stimulate individual thinking. Role model lecturers are inspiring to students. They should be individuals that are creative, have experience in entrepreneurial roles and hold academic knowledge that is useful to teach about entrepreneurship. There were variations in the views expressed by different groups of students interviewed in this study. Research limitations/implications: – Due to the relatively small sample sizes, this study has limited generalisability implying the need for similar research more broadly across other universities in Europe. Practical implications: – The study proposes a model for enhancing the teaching of entrepreneurial courses in universities in Europe. The model comprises teaching pedagogies responsive to the student learning needs; application of features present in the KTP model and proposes a structure for determining worthwhile knowledge that should be delivered in adherence to students learning needs. Originality/value: – This study expands the understanding of the learning process of students and provides a methodological framework that can be used to research entrepreneurial education.